Hypertension prevalence, awareness, treatment, and control in 115 rural and urban communities involving 47 000 people from China. Issue 1 (January 2016) - Li, Wei; Gu, Hongqiu; Teo, Koon K.; Bo, Jian; Wang, Yang; Yang, Jingang; Wang, Xingyu; Zhang, Hongye; Sun, Yi; Jia, Xuan; He, Xinye; Zhao, Xiuwen; et al.
Abstract : Background: Identification and treatment of hypertension in China remain suboptimal despite high prevalence of hypertension and increasing incidence of stroke and myocardial infarction. Objective: This study reported blood pressure levels, prevalence, awareness, treatment, and control rates of hypertension, in addition to drug treatments in China. Methods: This is a country-specific analysis of 45 108 individuals, average age 51.4 (standard deviation 9.6) (35–70) years, enrolled between 2005 and 2009, from 70 rural and 45 urban communities in 12 provinces. Results: Among 18 915 (41.9% overall population) hypertensive participants, 7866 (41.6%) were aware, 6503 (34.4%) treated but only 1545 (8.2%) controlled. Prevalence of hypertension was higher, but awareness, treatment, and control were lower in rural than urban residents. Prevalence of hypertension was highest in eastern (44.3%), intermediate in central (39.3%), and lowest in western regions (37.0%). Awareness was higher in central (44.3%) and eastern (42.4%) but lower in western regions (37.0%). Similar patterns were observed in treatment rates, 37.7% central, 35.2% eastern, and 26.7% in western regions with control rates of 8.3% in eastern, 7.6% central, and 5.3% west regions. Of 4744 participants receiving documented treatments, 37.5% received traditional combination drugs alone, 55.4% western drugs alone and 7.1% combination of traditional combination drug in addition to western drugs. Conclusion: In China, hypertension is common, and while recent studies suggest some improvements, more than half of affected individuals were unaware that they had hypertension. Rates of control remain low. National programs effective in preventing and controlling hypertension in China are urgently needed.